Självkostnadsprincipen vid entreprenad på löpande räkning - Entreprenörens beviskrav och beställarens kontrollrätt enligt 6 kap. AB 04 - Lehrecke,Ally (2025)
This thesis examines the self-cost principle as set out in the Swedish standard form contract AB 04 and the problems that often arise in connection with payment on a cost-reimbursable basis. Disputes between contractors and employers (clients) frequently concern which costs are reimbursable and how such costs can be proven. A central issue is the lack of a clear definition of what constitutes a “cost”, which creates uncertainty for both parties. The analysis shows that a reimbursable cost requires a factual economic sacrifice attributable to the specific contract. A cost must be connected to actual work performed or actual use of resources, and not merely recorded in ac-counting records without a corresponding factual economic sacrifice. As a result, the contractor´s cost documentation plays a key role in the assessment of reimbursement claims. The thesis further demonstrates that the contractor bears the burden of proof for showing that costs have arisen and are attributable to the project. In practice, the evidentiary assessment depends on whether the documentation is sufficiently transparent and project-specific to enable the employer to exercise its right of control under Chapter 6, Section 10, item 4 of AB 04. Finally, the thesis shows that the contractor´s duty of care under Chapter 6, Section 10, item 1 of AB 04 limits the right to reimbursement. The self-cost principle is thus based on an interaction between documentation, the employ-er’s right of control and the contractor´s duty of care. Reimbursement is granted only for costs that are attributable to the contract, verifiable, and actually incurred.
Keywords: avtalsrätt; civilrätt; entreprenadrätt; självkostnadsprincipen; entreprenadavtal